CdSe modified TiO2 nanotube arrays with Ag nanoparticles as electron transfer channel and plasmonic photosensitizer for enhanced photoelectrochemical water splitting. (10th July 2018) - Liu, Enzhou; Xue, Peng; Jia, Jia; Zhang, Xiaozhuo; Ji, Zhen; Fan, Jun; Hu, Xiaoyun
Abstract: Ag nanoparticles (NPs) and a CdSe nanocrystal were successively deposited on the surface of a TiO2 nanotube array film (CdSe/Ag/TiO2 NTs) via microwave assisted chemical reduction and in situ fabrication methods. The nanotubular structure of TiO2 preserves well after loading Ag and CdSe, as the ternary composite not only exhibits an excellent visible light harvesting ability but also has the smallest charge transfer resistance according to electrochemical impedance measurement. The most positive flat band potential of CdSe/Ag/TiO2 NTs facilitates charge carrier transfer at the semiconductor-electrolyte interface. Notably, the introduction of Ag nanoparticles forms a unique carrier-transfer-channel in the CdSe/Ag/TiO2 NTs system, in which the Ag nanoparticles can take advantage of its high carriers transfer rate as a linker. In addition, Ag serving as a surface plasmon resonance source further improves photoelectric catalytic activities of the sample. It is noteworthy that CdSe/Ag/TiO2 NTs exhibits the desired photoelectrochemical performance with the highest H2 production rate of 413.99 µ mol cm −2 after 2.5 h irradiation.